The Influence of Digital Technology Adoption by Small and Medium Enterprises and Online Consumer Behavior on the Success of E-commerce Platforms in Bandung City - Ambar Kusuma Astuti; Edhi Juwono; Teguh Setiawan Wibowo (West Science Journal Economic and Entrepreneurship, 2023)
This study looks into the complex relationships that exist between the use of digital technology by Small and Medium Enterprises (SMEs) in Bandung City, online consumer behavior, and the performance of e-commerce platforms. Through the use of structured surveys and a quantitative approach, information about digital technology integration, online customer behavior patterns, and markers of e-commerce success was gathered from 121 SMEs. The results show that consumer behavior dynamics are diverse, there is a moderate level of acceptance of digital technology, and both characteristics have a considerable beneficial impact on the performance of e-commerce. The key component that emerges is trust, underscoring the significance of building customer confidence in the digital economy. The study adds to our knowledge of the complex interactions that occur between customer engagement and technology adoption, providing SMEs navigating the digital landscape with useful insights.